2016
DOI: 10.1007/s00027-016-0488-x
|View full text |Cite
|
Sign up to set email alerts
|

Native submerged macrophyte distribution in seasonally-flowing, south-western Australian streams in relation to stream condition

Abstract: Submerged macrophytes are important structural and biological components of many lowland streams with potential to support ecosystem processes in degraded streams, provided that growth is not excessive. In a low-gradient agricultural landscape, a survey was used to explore associations between submerged macrophyte growth, biodiversity and variables assessing stream condition in seasonally-flowing streams.These variables were sampled across fifty-three reaches on seven adjacent streams in the mediterranean clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…The habitat association of dragonflies and damselflies in Africa has been described by many researchers (e.g., Vorster et al, 2020). Moreover, several studies have shown that species assemblages of odonates are influenced mainly by aquatic and terrestrial vegetation (Paice, Chambers, & Robson, 2017). Studies have shown that adult diversity and abundance is often positively correlated with local abundance of vegetation (Remsburg & Turner, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The habitat association of dragonflies and damselflies in Africa has been described by many researchers (e.g., Vorster et al, 2020). Moreover, several studies have shown that species assemblages of odonates are influenced mainly by aquatic and terrestrial vegetation (Paice, Chambers, & Robson, 2017). Studies have shown that adult diversity and abundance is often positively correlated with local abundance of vegetation (Remsburg & Turner, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Aquatic submerged macrophytes support many important services in stream ecosystems. They provide food and habitat for invertebrates and fish [ [1] , [2] , [3] , [4] ], alter the physico-chemical environment [ 5 ] and affect nutrient cycling [ 6 ]. However, increased anthropogenic influences have impacted stream macrophyte communities and the services they support [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%